PENGARUH QUALITY DAN CREDIBILITY ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE - Rena Feri Wijayanti; Lina Budiarti; Joni Dwi Pribadi; Sanita Dhakirah (J-MACC, 2025)
The purpose of this study is to analyze the quality of information on e-WOM and also the credibility of e-WOM on online purchasing decisions focused on the Shopee Marketplace. This study uses a quantitative approach with a sample size of 100 respondents and purposive sampling is used in this research. Data analysis was carried out starting from testing the validity and reliability of the questionnaire and continuing with the analysis of the classical assumption test, multiple regression analysis, t-test, and the F-test with SPSS for Windows tools. The results of the data test show that this research questionnaire is valid and reliable. Furthermore, it can be explained that the quality and credibility of e-WOM have a positive and significant influence on purchasing decisions.